Microplastic abundance in sea urchins (Diadema setosum) from seagrass beds of Barranglompo Island, Makassar, Indonesia. Issue 1 (May 2021) - Sawalman, R; Werorilangi, S; Ukkas, M; Mashoreng, S; Yasir, I; Tahir, A
Abstract: High levels of anthropogenic activities on Barranglompo Island in Makassar City, South Sulawesi Province, Indonesia increase the amount of plastic waste in the surrounding waters, especially in seagrass beds. Plastic waste becomes fragmented into small particles called microplastics (MPs). Sea urchins (Echinoidea), as organisms associated with seagrass beds, can accumulate microplastics through their feeding habits. This study aimed to determine the abundance and characteristics of microplastics accumulated in sea urchins ( Diadema setosum ), seagrass leaves, and sediment. Samples (urchins, seagrass leaves, and sediment) were collected from a multi-species ( Enhalus acoroides and Thalassia hemprichii ) seagrass bed where D. setosum was present. The internal organs of the sea urchins were extracted using a KOH 10% solution to degrade organic materials. The seagrass leaves were rinsed using distilled water and stirred using a shaker rotator. MPs in sediment were separated using ZnBr2 . MPs in all samples were identified visually under a stereomicroscope. The results show that all (100%) sea urchins samples (n=10), seagrass leaves (n=24), and sediment samples (n=8) were contaminated by MPs. The average MP abundance was 23.70±2.99 items/individual in D. setosum ; 0.10±0.02 items/cm 2 and 0.24±0.05 items/cm 2 respectively on E. acoroides and T. hemprichii leaves; and 195±66.98 items/kg of dry weight in the sediment. The MPs found shared similar characteristics such as colour (predominantly blue) and shape (dominated by line).